IMPLEMENTATION OF PSAK 109 CONCERNING REPORTING OF ZAKAT FUNDS, INFAQ/ALMS AT THE NATIONAL AMIL ZAKAT AGENCY FOR MALANG CITY - Mufidah, Putri Nur; Djalaluddin, Ahmad (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The purpose of this study is to find out whether BAZNAS Malang City has properly recorded its financial reports in accordance with PSAK109 which has been determined by the Indonesian Institute of Accountants (IAI). BAZNAS is not a profit-oriented organization that collects funds from the public and then distributes them to those who are entitled to receive them. Therefore everything that exists must be reported transparently to the public. In managing Zakat funds, you should be able to present reports with the method of recording and appearance of entities in accounting, such as assets and liabilities that are grouped according to the use of each item.In entering BAZNAS data using the SIMBA application. BAZNAS Malang City has recorded transactions with accrual recording and the recording is done separately between zakat funds and infaq/alms funds. Financial reporting is also carried out separately between statements of financial position, reports on changes in funds, reports on assets under management, reports on cash flows and notes on financial statements. And the disclosure is also in accordance with what is in the field.